POLICY INSTRUMENTS OF PERSUASION AND COERCION: LESSONS FROM ZIMBABWE GOLD CURRENCY REFORM (2024–2025) - Malony Zorodzai Marekwa; Asal Wahyuni Erlin Mulyadi; Rino Ardhian Nugroho (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The policy implementation process is complex, as policymakers select and design policy instruments that best suit their objectives in the context of the issues at hand. This study explores how the Zimbabwean government implemented the 2024 Zimbabwe Gold currency reform through persuasion and coercion in a low-trust economy with a highly informal structure. This study uses policy instrument theory and the NATO framework to argue that policy instruments based on nodality can be deployed as persuasion and those based on authority as coercion. This study employs reflexive thematic analysis across 30 documents from government, civil society, academia, and the media. The results show that using nodality tools, such as persuasion without transparency, is a symbolic mechanism, and using authority-based tools without capacity is a coercive mechanism that is difficult to implement. The joint application of the two instruments in these cases reduces the effectiveness of the policy, promotes informality, and weakens citizens’ trust in public institutions. The study concludes that persuasion and coercion are insufficient substitutes for credible institutional frameworks and stakeholder engagement. This study contributes to policy instrument theory and offers recommendations for currency reforms in developing countries.